Методики розрахунку інтелектуального потенціалу підприємства - Марчук, Леся Сергіївна (НТУ "ХПІ", 2018)
Інтелектуальний потенціал в управлінській діяльності підприємства відіграє досить важливу роль, адже має цілий ряд специфічних особливостей: навички, здібності, компетенції, трудові та інтелектуальні ресурси, знання, ідеї, технології, інтелектуальний капітал і т. д. Саме це потребує пошуку методичних підходів для розрахунку інтелектуального потенціалу підприємства. У статті проведено аналіз методів оцінювання інтелектуального потенціалу, який довів, що на сьогоднішній день не існує єдиної та максимально точної системи розрахунку. Визначено суттєві недоліки досліджених методик та запропоновано шляхи їх удосконалення.

Intellectual potential in the management of the enterprise plays a very important role, because it has a number of specific features: skills, abilities, competences, labor and intellectual resources, knowledge, ideas, technology, intellectual capital, etc. That is precisely what needs to be done to find methodological approaches for calculating the intellectual potential of an enterprise. Consequently, in today's conditions, the assessment of intellectual potential is a key task for the successful operation and competitiveness of any industrial enterprise. Given the current state of development of the production of goods and services, it can be argued that knowledge is the main source of productivity. This knowledge (abilities, skills, skills, professional qualifications, organization's image, patents, licenses, investments, innovations, creativity and creativity of thinking) in aggregate represent the intellectual potential The article analyzes the methods of estimating intellectual potential, which proved that for today there is no single and maximally accurate system of calculation. The essential disadvantages of the investigated techniques were determined and ways of their improvement were proposed.
Methods of calculation of intellectual potential of enterprise
Keywords: інноваційний розвиток; кількісний розрахунок; інтеллектуальні ресурси; людський капітал; інтеллектуальна власність; споживчий капітал; intellectual potential; methods and approaches of calculation; estimation